Pengaruh Komunikasi terhadap Kinerja Karyawan pada Hotel Tentrem Yogyakarta - Hadyan Wahyu Dewanto; Irene Hanna H. Sihombing; Ida Ayu Kalpikawati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Communication plays a crucial role in influencing employee performance. Performance decline is often caused by communication issues, particularly in the hotel back office, such as the lack of effectiveness in information delivery and miscommunication among employees. This study aims to analyze the impact of communication on employee performance at Hotel Tentrem Yogyakarta. The data used includes quantitative data from employee performance evaluations in 2023, the number of employees, employee communication levels from 2019-2023, and qualitative data from interviews with human resources. The study population consists of 241 employees at Hotel Tentrem Yogyakarta. Data was collected using documentation and questionnaires distributed to respondents. Data analysis techniques include validity testing, reliability testing, normality testing, heteroskedasticity testing, simple linear regression, t-test, and coefficient of determination (R²). The study findings show that the calculated t value (38.728) is greater than the t table value (0.1264) with a significance level of 0.000, indicating a positive and significant effect of communication on employee performance at Hotel Tentrem Yogyakarta. The coefficient of determination value of 0.863 indicates that 86.3% of the impact on employee performance is due to communication, while 13.7% is influenced by other factors outside the scope of this study.